The significance of C-reactive protein for the prediction of net-adverse clinical outcome in patients with acute pulmonary embolism - Milić, Rade; Džudović, Boris; Subotić, Bojana; Obradović, Slobodan; Soldatović, Ivan; Petrović, Marina (Vojnosanitetski pregled, 2021)
Background/Aim. Acute pulmonary embolism (APE) may have different clinical manifestations. Also, its outcome can range from complete recovery to early death. Major bleeding (MB) as a due of the therapy also contributes to the overall adverse outcome. So far, it is unknown what the best predictors are for short-term mortality and MB among the several commonly used biomarkers. The aim of this study was to evaluate the significance of C-reactive protein (CRP) and other biomarkers for the prediction of adverse clinical outcomes. Methods. This clinical, observational, retrospective-prospective study included 219 consecutive adult patients treated for APE. Results. Among 219 patients, 22 (10%) died within the first month after diagnosis. Twenty seven patients (12.3%) had at least one episode of MB. Composite end-point [net-adverse clinical outcome (NACO)] was estimated in 47 (21.5%) of patients. The average values of all biomarkers were higher in the group of patient who died, and differences were statistically significant. Similar results were obtained for composite end-point. In terms of MB, none of biomarkers did not have significance, but CRP had a slight tendency toward significance. Results from univariate logistic regression model showed that troponin was statistically significant predictor of 30-day mortality. However, after adjusting for other variables, in multivariate logistic regression model troponin failed to be significant independent predictor of 30-day mortality. Unlike troponin, CRP and brain natriuretic peptide (BNP) were significant in all models – uni and multivariate (they were independent predictors of 30-day mortality). Conclusion. CRP has a good predictive value for 30-day mortality and NACO, and potential for MB in patients treated for APE.
Keywords: c-reactive protein; mortality; prognosis; pulmonary embolism; treatment outcome